Tribo-electrostatic separation of a quaternary granular mixture of plastics. (18th August 2019) - Messafeur, Radjaa; Mahi, Imene; Ouiddir, Rabah; Medles, Karim; Dascalescu, Lucien; Tilmatine, Amar
ABSTRACT: Many tribo-electrostatic separation studies of binary mixtures of millimeter-sized plastic particles have been performed. The objective of this work is an experimental investigation for separating a quaternary mixture comprising four different plastic types issued from waste electrical and electronic equipment. The feasibility of the separation of such quaternary mixtures by the sliding mode tribocharging with a metal wall was demonstrated. The separation of a mixture comprising PA, PC, high impact polystyrene, and polyvinyl chloride granules is better in terms of both purity and recovery when charging the particles by sliding contact with the metal wall, then in the case of a fluidized bed device.